An OSCE Evaluation Tool for the Assessment of Emergency Medicine Resident Progression Performance of ACGME Patient Case and Interpersonal Communication Milestones - Miriam Kulkarni; Tiffany Murano; Harsh Sule; Jill Ripper; Gregory Suglaski (eScholarship Publishing, University of California, 2018)
Audience: This curriculum is designed to provide a standardized assessment of Emergency Medicine resident performance of selected ACGME Patient Care and Interpersonal Communication Milestones in Emergency Medicine. Introduction: Since the development of the Milestones in Emergency Medicine, residency educators have found assessment of milestones in the clinical setting challenging.1 We piloted an Observed Standardized Clinical Evaluation (OSCE) based on selected milestones in Emergency Medicine. We chose to evaluate Patient Care and Interpersonal Communication milestones because we felt that these milestones are easiest to assess using an OSCE model. There is also some evidence that patient care milestones are difficult to reliably assess in the clinical setting.1 Objectives: Our goal was to create a standardized OSCE based formative assessment tool that could be deployed with minimal resource utilization. The purpose of our tool is to provide data regarding Emergency Medicine Residents' performance in ACGME patient care milestones as they progress longitudinally through their residency. Method: The sources of multi-source feedback used in this curriculum include direct observation of the residents' history and physical exam performed on a standardized patient, evaluation of the residents' interpretation of visual stimuli such as EKGs and radiographs, and interaction with simulated consultants. Feedback was provided during the encounter by both faculty and the standardized patient.